2012
DOI: 10.2105/ajph.2012.300725
|View full text |Cite
|
Sign up to set email alerts
|

Parental Characteristics Associated With Bullying Perpetration in US Children Aged 10 to 17 Years

Abstract: Assessing children's EDB problems, maternal mental health, and parental perceptions may identify children at risk for bullying. Parent-child communication, meeting children's friends, and encouraging children academically were associated with lower bullying odds; these protective factors may be useful in designing preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
1
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 37 publications
6
48
1
19
Order By: Relevance
“…With regard to students who practiced bullying, REV BRAS EPIDEMIOL SUPPL PeNSE 2014; 92-105 the opposite was observed: their mothers had higher schooling, and this result was found in other studies 21,23 . That is, higher maternal schooling proved to be a protective factor against suffering bullying, which is confirmed by a study that points out that children coming from family contexts with restricted cultural capital, who are little encouraged and followed-up by their parents in their academic tasks, and whose parents do not talk or share ideas with them, have higher chances at bullying 25 . It is confirmed, therefore, that the role of parents and family groups should also be valued in investigations and interventions about development, maintenance and prevention of bullying 26,27 .…”
Section: Discussionmentioning
confidence: 72%
“…With regard to students who practiced bullying, REV BRAS EPIDEMIOL SUPPL PeNSE 2014; 92-105 the opposite was observed: their mothers had higher schooling, and this result was found in other studies 21,23 . That is, higher maternal schooling proved to be a protective factor against suffering bullying, which is confirmed by a study that points out that children coming from family contexts with restricted cultural capital, who are little encouraged and followed-up by their parents in their academic tasks, and whose parents do not talk or share ideas with them, have higher chances at bullying 25 . It is confirmed, therefore, that the role of parents and family groups should also be valued in investigations and interventions about development, maintenance and prevention of bullying 26,27 .…”
Section: Discussionmentioning
confidence: 72%
“…In this regard, a study has evidenced that the scale of bullying perceived by caregivers tends to be lower than that reported by children. 4 On their side, Shetgiri et al 3,5,13,14 concluded that caregivers are often unaware of the fact that their children are the victims of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the authoritative parental style was negatively linked to children's involvement in bullying. In the same line, Shetgiri et al [12] showed that parents who talked with their children and met all or most of their friends had children with lower bullying odds. The same researchers also found that parents who felt angry with their children or felt that their children bothered them had children with higher bullying odds.…”
Section: Parental and Peer Correlates Of Bullyingmentioning
confidence: 92%
“…Thus, it is now widely believed that the contextual factors such as maladaptive parental characteristics and peer relationships may increase the chances of children's involvement in bullying [11][12][13]. Georgiou [11] has reported that the authoritarian parental style was associated with higher levels of bullying, while the permissive parental style was associated with victimization.…”
Section: Parental and Peer Correlates Of Bullyingmentioning
confidence: 99%